The Relationship Between Stress Level During the Covid-19 Pandemic with Fluor Albus Incidence in Adolescent - Dina Afkarina; Dini Kurniawati; Iis Rahmawati (KHD-Production, 2022)
Fluor Albus is a condition that is often complained of by women, especially teenagers. Fluor albus can be affected by stress because it can affect changes in the hormonal balance in the body. Meanwhile, the Covid-19 Pandemic condition can be a stressor for a person and if it is not handled properly it will affect the body's condition, one of which is the influence of hormone balance in the body which can lead to Fluor Albus Incidence. This study aims to determine the relationship between Stress Levels during the Covid-19 Pandemic Period with Fluor Albus Incidence in adolescent students at the Nuris Islamic Boarding School Jember. This study used an analytical observational design with a cross-sectional approach. A total of 107 students of the Nuris Jember Islamic boarding school who were included in this study used purposive sampling as a sampling technique. The instruments used in this study were the COVID-19 pandemic stress level questionnaire and the vaginal discharge questionnaire. The results showed that the majority of adolescents (72%) experienced normal levels of stress and experienced normal occurrences of fluor albus (54,2%). Bivariate analysis was performed using the chi-square test which showed that p<0.05 with p=0.003. There is a Relationship between Stress Levels during the Covid-19 Pandemic and Fluor Albus Incidence in Adolescent at the Jember Nuris Islamic Boarding School. It is hoped that teenagers will try to maintain their reproductive health and try to manage stress during the Covid-19 pandemic.